Undergraduate Students’ Perception on Videotaping - Batunan, D A (Journal of Educational Method and Technology, 2019)
The industrial industry has influenced humans’ lives and changed many aspects including the way how people learn. It is a challenge for the teachers to integrate technologhy into their classrooms. Reading activities on the FL classrooms should not tend to be reading texts and answering a series of questions anymore. The purpose of this study is to explore students’ perception on the implementation of videotaping. Twenty five students’ perception on it were explored through the use of interviews. The result showed that the students had a positive atitude toward it despite the fact of some issues might arise like tecnical, content and delivery.    Keywords: Videotaping, perception, creativity, self-reflection